The impact of ISO 14001 environmental standards on exports - Juan S. Blyde (Inter-American Development Bank (IDB), 2021)
Analyses that examine the role of international standards on export performance has been concentrated on quality certifications. Very little is known about the impact of environmental certifications on exports. In this paper we employ firm-level data from Ecuador to assess the impact of the ISO 14001 environmental certification on export outcomes. The results show that holding an ISO 14001 increases the likelihood of becoming an exporter by 0.31 percentage points (equivalent to 4%), and that this positive effect is concentrated among large firms. We did not find evidence that the environmental certification has a causal impact on the level or the growth rate of exports. Consequently, the results suggest that the ISO 14001 certification is most useful in reducing information frictions, allowing firms to initiate export transactions.
Keywords: F14; F18; Q56; 330; Exports; environmental standards